DIMENSI KREATIF DALAM PEMBELAJARAN PENDIDIKAN JASMANI DI SEKOLAH - Rachman, Hari Amirullah (Jurnal Pendidikan Jasmani Indonesia, 2010)
Abstract Every child is born with creative potential, but this potential may be stifled if care is not taken to nurture and stimulate creativity. Creativity is the ability to see things in a new and unusual sight, to see problems that no one else may even realize exist, and then come up with new, unusual, and effective solutions to these problems. Children like to try out different ways, experiment with different materials, and see what they can do creatively. Finding different ways to exspressing themselves physically satisfies the urge for creative action. But it must be their ways, their ides, and their accomplishment. Physical education gives children opportunity for exploratory and creative activity. Children need an opportunity to tray out their own ideas, solve some of their own movement problems and bring forth movement of their own origin. Teachers need to take advantage of this drive by providing opportunity for the child to come up with his own movement ideas. Kata kunci: Kreatifitas, pembelajaran pendidikan jasmani